The Phenotypic Spectrum of ZIC3 Mutations Includes Isolated d-Transposition of the Great Arteries and Double Outlet Right Ventricle - D’Alessandro, Lisa C. A. (2013)
Disease causing mutations for heterotaxy syndrome were first identified in the X-linked laterality gene, ZIC3. Mutations typically result in males with situs ambiguus and complex congenital heart disease; however affected females and one male with isolated d-transposition of the great arteries (d-TGA) have been reported. We hypothesized that a subset of patients with heart defects common to heterotaxy but without laterality defects would have ZIC3 mutations. We also sought to estimate the prevalence of ZIC3 mutations in sporadic heterotaxy. Patients with TGA (n=169), double outlet right ventricle (DORV) (n=89), common atrioventricular canal (CAVC) (n= 41) and heterotaxy (n=54) underwent sequencing of ZIC3 exons. We tested 90 patients with tetralogy of Fallot (TOF) to correlate genotype with phenotype. Three potentially disease-related missense mutations were detected: c.49G>T (Gly17Cys) in a female with isolated DORV, c.98C>T (Ala33Val) in a male with isolated d-TGA, and c.841C>T (His281Tyr) in a female with sporadic heterotaxy. We also identified a novel insertion (CPFP333ins) in a family with heterotaxy. All were absent in 200 control patients and the 1000 Genomes Project (n = 629). No significant mutations were found in patients with TOF. Functional studies demonstrated reduced transcriptional activity of the ZIC3 His281Tyr mutant protein. ZIC3 mutations were rarely identified in isolated DORV and d-TGA suggesting that a subset of DORV and d-TGA may fall within the spectrum of laterality defects. ZIC3 mutations were found in 3.7% of patients with sporadic heterotaxy; therefore testing should be considered in patients with heterotaxy.